MANETs: How are they evolving to support multimedia communication? - Dimitris Kanellopoulos (Trends in Computer Science and Information Technology - Peertechz Publications, 2020)
This short paper discusses critical issues of multimedia over Mobile ad hoc Networks (MANETs) focusing on the Quality of Service (QoS) support for wireless multimedia transmission. The paper explains how MANETs are evolving to support multimedia communication. In particular, it briefly presents some novel approaches that can improve the performance of MANETs when multimedia transmissions take place.